FAKTOR – FAKTOR YANG MEMPENGARUHI PENGENDALIAN KUALITAS BABY BUNCIS UNTUK MEMENUHI PASAR EKSPOR - Nadapdap, Hendrik Johannes (CEFARS : JURNAL AGRIBISNIS DAN PENGEMBANGAN WILAYAH, 2012)
Globalization era resulted in a change for all countries in the world in International trade. International trade is demanding quality standards.The main export destinations Singapore and Japan. Singapore is the country's biggest importer of beans. Singapore interested in the baby beans product from Indonesia. This study aims to determine the factors that influence the quality conrol of baby bean in fulfilling the export market. A method used in this research is the census method with descriptive analysis as the techniques of analysis. This research obtains seven factors which cause an adequate affectation to the quality control of baby beansthose are pests and diseases, harvests, standard of quality, ability of farmers, expenses, seasons, and post-harvest.